THE RELATIONSHIP OF HEALTH THERAPEUTIC COMMUNICATION TROUGH PATIENT’S SATISFACTION ON HEALTH SERVICE IN PMI HOSPITAL ROOM, BOGOR: HUBUNGAN KOMUNIKASI TERAPEUTIK TENAGA KESEHATAN DENGAN KEPUASAN PASIEN TERHADAP PELAYANAN KESEHATAN DI RUANG RAWAT INAP RS PMI KOTA BOGOR - Deden Nurjaman; Dede Rukasa (Jurnal Ilmiah Wijaya, 2018)
Therapeutic communication is the one of the standards of nursing care that must be implemented by all nurses. The good implementation of therapeutic communication can increase the satisfaction of nursing care perceived by patients. Knowing the relationship between therapeutic communication with patient satisfaction inCempaka room PMI Hospita, Bogor.Typeof thisresearch is using random sampling technique with the descriptive analytical method and the cross sectionaldesign. To collect the data, the researcherusing questionnaire instrument on two variablesas follow therapeutic communication of nursing and patient satisfaction questionnaire instrument. Theresearch site of this research is held at PMIHospital Bogor on October, 2018 with patients in the Cempaka room PMI HospitalBogorwho have experienced 85 respondances were brought into the hospital. Analysis techniques using univariate and bivariate analyzers with kendaal’s tau-c statistics test.The resultOf the 96 respondents found that did therapeutic nursing communication applied amounted to 38 respondances (65,5%). And patiens say satisfied with the nursing services amounted to 40 respondances (69,0%).On the statistics test is gotten that P Value 0,001. Ha is accepted and Ho is rejected that P Value <0,05.